Comparative Space Law : The Space Frontier from a Private Law Perspective - Zolea, Sirio, (International Law E-Books Online, Collection 2025., 2025)
This book approaches space law from the angle of legal comparison. In a new phase of exploration and exploitation of outer space characterised by an increasing presence and role of commercial entities, problems inherent in systems of private law arise in a special context and require specific legal answers. Through a comparative method, this book systematises the complex legal spacescape concerning some fundamental concepts rooted in the various national systems of private law: natural and legal persons, property rights, liability, contracts, and securities. These analyses form a handbook of private law in the context of outer space.